(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Abstract: This study examines the economic strategies and resilience of Internally Displaced Persons (IDPs) in Greater-Kasai (DRC), a region scarred by protracted conflict and humanitarian crises. It investigates informal survival mechanisms (subsistence farming, petty trade, crafts), community networks, and structural barriers (insecurity, land scarcity, institutional gaps). Methodology: Mixed-methods approach (quantitative surveys, qualitative interviews, participatory mapping) grounded in theories of informal economies and social capital. Key Findings: • 87% of IDP income derives from the informal sector, yet with heightened vulnerability. • Women (53.2% of IDPs) drive resilience but face disparities (limited credit access, unpaid labor). • Community networks (cooperatives, savings groups) enhance stability but lack legal recognition. • Humanitarian aid is critical but risks dependency without sustainable solutions (microfinance, land reform). Recommendations: • Formalize informal economies through legal cooperatives. • Improve access to land and basic services (water, education). • Mainstream IDPs into local development plans. • Implement gender-responsive interventions to empower women.